The Feasibility Of ‘Tell Me More’ Oral Activities In Developing UTM Students’ Speaking Skill - Md. Yusof , Masdinah Alauyah; Mohamad Borhan, Isni Mimiyana (2010)
English speaking skill is becoming more important among university students. Through the Faculty of Management and Human Resource Development (FPPSM) UTM, the Self-Access Learning is introduced into the English proficiency courses. Tell Me More is one of the software that provides the activities for the students to improve their English speaking skill. The use of this software inspired the researcher to find out its feasibility in developing UTM students’ speaking skill. A total of 70 students who were involved in the research were asked to fill up the questionnaire. As a whole, students agreed with the use of Tell Me More in helping them to enhance their English speaking skill. The feedbacks received provide useful information about i) students’ perception of the Tell Me More oral activities, and ii) the problems that students faced while using the software. Apart from that, the researcher has given a few recommendations that can be used for the future research which related to the topic of this study.